Constituting and administering the ecological politics by the civil service in Poland and of the European Union - Jabłoński, Maciej (Studia Ecologiae et Bioethicae, 2011)
Environmental protection is a field of law about interdisciplinary character, which using notions typical of legal, natural, technical, or chemical theories is a rule in. Therefore in practice, they can have the notional various meaning depending on the context they stayed in which used. A notion which is paying attention to the rights and duties of citizens, bodies of a public authority or also environmental organizations, is an ecological politics.